Cetyltrimethylammonium Bromide-Modified LaponiteDiatomite Composites for Enhanced Adsorption Performance of Organic Pollutants - Dai, Nan (Langmuir : the ACS journal of surfaces and colloids, 2024)
This work aims to enhance the adsorption performance of Laponite diatomite for organic pollutants by modifying it with cetyltrimethylammonium bromide (CTAB). The microstructure and morphology of the CTAB-modified Laponite @diatomite material were characterized using SEM, XRD, FTIR, BET, and TG. Furthermore, the influences of key parameters, containing pH, adsorbent dosage, reaction time, and reaction temperature, on the adsorption process were investigated. The kinetics, thermodynamics, and isotherm models of the adsorption process were analyzed. Finally, potential adsorption mechanisms were given based on the characterization. The research findings indicate that CTAB-La@D exhibits good adsorption performance toward Congo red (CR) over a broad pH range. The maximum adsorption capacity of CR was 451.1 mg/g under the optimum conditions (dosage = 10 mg, contact time = 240 min, initial CR concentration = 100 mg/L, temperature = 25 °C, and pH = 7). The adsorption process conformed to the pseudo-second-order kinetic model, and the adsorption isotherms indicated that the adsorption process of CR was more in line with the Langmuir model, and it was physical adsorption. Thermodynamic analysis illustrates that the adsorption process is exothermic and spontaneous. Additionally, the mechanisms of electrostatic adsorption and hydrophobic effect adsorption of CR were investigated through XPS and FTIR analysis. This work provides an effective pathway for designing high-performance adsorbents for the removal of organic dye, and the synthesized materials hold great capability for practical utilization in the treatment of wastewater